The Ratio and Rasa Paradigm: Educational Discipline In OPPM's Decision-Making On Student Violations at Pondok Modern Darussalam Gontor - Ilman Hafidzul Huda; Wahyu Setiawan; Sutrisno Ahmad; Idam Mustofa; Syarifah Syarifah (Universitas Nurul Jadid, 2025)
This study aims to analyze the paradigm of educational discipline in the decision-making process of the Modern Islamic Boarding School Student Organization (OPPM) regarding student disciplinary violations at Pondok Modern Darussalam Gontor. The study is motivated by a disciplinary system that emphasizes not only rule enforcement but also character development and educational considerations. This research employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and document analysis involving OPPM administrators, student affairs officers, teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that disciplinary decisions within OPPM are based on the integration of two key considerations: reason and empathy. Reason is reflected in fact verification, adherence to institutional regulations, and compliance with standard operating procedures (SOPs), while empathy is reflected in clarification processes, understanding the context of violations, and educational considerations aimed at student development. The integration of these two dimensions forms an educational discipline paradigm that views discipline as a means of character education rather than merely a punitive mechanism. This study proposes the concept of the Reason and Empathy Paradigm as a disciplinary decision-making model that integrates rule-based objectivity with educational considerations to foster students’ character development.